Modelling of a multistage reciprocating humidifier and performance analysis for various packing configurations. (15th February 2022) - Salins, Sampath Suranjan; Reddy, S.V. Kota; Kumar, Shiva
Abstract: Excessive energy consumption has led to environmental problems and climate change. Cooling of the building is the key reason for energy consumption in hot regions. Due to the consistent sunlight intensity and high temperatures, the use of cooling units are inevitable. Single stage humidifiers are widely used which provided evaporative cooling consistently. Present work focuses on designing and fabricating a novel multistage reciprocating humidifier operated by a cam follower mechanism. Four packings are operating at four different positions in dynamic conditions. A theoretical model has been constructed to predict the thermal performance parameters using commercially available celdek packing 7090, 5090, honeycomb and corrugated. Theoretically predicted results agree with the experimental results with a maximum deviation of 2.1%., 4.8% and 8.6% for DBT, humidity ratio and saturation efficiency. Variation of the results is studied stage wise, and its change in performance is analyzed. Simulated results indicated that celdek 7090 outperformed the others in terms of change in dry bulb temperature, humidity ratio and saturation efficiency by 0.6%, 0.8% and 1.2% for the airflow rate of 5.6 m/s, respectively. Increasing the pad thickness showed improvement in the drop in dry bulb temperature, increased humidity ratio, and saturation efficiency. It is recommended to use zig-zag celdek 7090 type with 15 cm thickness in a multistage cooler to obtain the best performance for cooling applications in buildings with less cost. Highlights: A mathematical model for a multistage reciprocating humidifier has been constructed. Model predicted results are validated by comparison with the experimental values. Influence of the various types of celdek configuration on the performance has been analyzed. Celdek packing 7090 with 15 cm thick packing gives better results compared to other packing types.